Perceptions of University Professors on the Purposes of Higher Education: Some Preliminary Results for a Fundamental Question - Espejo Leupin, Roberto (2024)
This article presents the perceptions regarding the purposes of higher education from a group of 48 faculty members at a private Chilean university. The study reviewed specialized literature and each researcher established an individual selection of potential educational purposes of higher education, which were then socialized and discussed to define a proposed set of seven concepts based on the researchers' criteria. These concepts were presented to the faculty group, who were asked to prioritize them according to importance through an online questionnaire. The study follows a positivist paradigm with a non-experimental descriptive, comparative, and cross-sectional design. Data were analyzed based on the importance attributed by faculty members to each concept, categorizing them into a central zone and two peripheral zones through cluster analysis. The results highlight the centrality attributed to the development of critical thinking, ethical attitude, and autonomy, while concepts such as social commitment, citizenship competencies, self-determination, and professional technical competencies are more peripheral. These findings vary according to different levels of teaching experience and disciplinary type, except for critical thinking development, which maintains its central position. The study underscores how such descriptions can serve as a tool to enhance faculty development processes and emphasizes the need to complement these results with qualitative techniques and longitudinal studies.